COMPARACIÓN DE DOS TÉCNICAS PARADETERMINAR LA DIGESTIBILIDAD PROTEICADE INSUMOS YALIMENTOS COMERCIALES PARA CANINOS - Malca O., Sandra (2012)
The aim of this study was to compare the in vivo apparent protein digestibility method in rats and the in vitro pepsin digestibility method as well as their level of correlation. Three protein sources used in commercial dog foods (soybean meal, meat meal, and chicken meal), three commercial adult dog foods (A1, A2, and A3), three commercial puppy foods (C1, C2, and C3), and sodium caseinate as a control groupwere evaluated. For the in vivo assay, 60 twenty-three-day-old albino laboratory rats (Rattus norvegicus) were used and for the in vitromethod the standardized pepsin method used at the Nutrition Laboratory, Faculty of Veterinary Medicine, UNMSM was evaluated. The correlation coefficient between the in vivo and in vitro methods was 0.94, whereas the in vitro digestibility was statistically higher than the in vivo digestibility (p<0.05). The regression equation was Y, in vivo = 11.037 + 0.804 (X, in vitro). It was concluded that there is a high correlation between both protein digestibilitymethods when assessing protein sources and commercial dog foods.